(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: Measles is one of the leading causes of childhood mortality worldwide. A live-attenuated vaccine controls measles infection in industrialized countries, and measles has been targeted by the WHO for global eradication following the eradication of poliomyelitis. Objective: To determine the antibody response to measles virus in seropositive volunteers after vaccination with live attenuated measles vaccine. Methods: Fifty two measles virus seropositive normal volunteers have been enrolled in this study, they were 36 males and 16 females, their age ranged between 15-45 years. 26 of them were vaccinated with measles virus vaccine and 26 were injected with diluent supplied with measles virus vaccine (placebo). Antibodies against measles virus were detected in volunteer’s sera prior to, one and four weeks after vaccination, using ELISA method. Results: There was marked rising in the mean of antibodies after vaccination, the OD readings were 1.72 and 1.95 during first and fourth week respectively. Data analysis showed that there was a significant difference of OD value among seropositive vaccines. And there was a significant elevation of serum antibody in the first week, but the fourth week had very high OD readings, which may reflect an increase in the concentration of antibodies. Conclusion: Measles virus vaccine was safe, and at the same time effective. There was no evidence of transient suppression of the humoral immune response and there was an elevation of serum antibody titer among vaccinated individuals. Key words: Antibody, seropositive, measles vaccination Iraqi J Med Sci, 2004; Vol. 3 (1): 26-28